PREDICTORS OF COGNITIVE DETERIORATION DURING THE FIRST YEAR AFTER ISCHEMIC NON-LACUNAR STROKES IN PATIENTS WITH ATRIAL FIBRILLATION - Delva, Mykhaylo; Zayets, Victoria; Chekalina, Natalya; Delva, Iryna (Eastern Ukrainian Medical Journal, 2025)
Introduction. Epidemiological studies revealed that AF may be an independent predictor of cognitive impairment, including post-stroke patients. AF patients had statistically significant deterioration of cognitive functioning during the first year after ischemic strokes. However, the factors associated with cognitive deterioration during the post-stroke period in AF patients have not yet been identified. Objective: to study the factors associated with cognitive deterioration during the first year after ischemic non-lacunar strokes in patients with AF. Materials. In the final analysis, we included 65 patients with AF who had an ischemic non-lacunar stroke within the last 6 months. The cognitive assessment consisted of a Mini-Mental State Examination, Montreal Cognitive Assessment, Clock Drawing Test, and Frontal Assessment Battery. “Cognitive deterioration” was defined as ≥ 1 point decrease by any of the cognitive scales at the 12-month visit compared to the initial visit score. As predictors of cognitive deterioration, we studied socio-demographic, psycho-emotional, comorbid, neurological, functional, neuroimaging factors, lipid profile, and transthoracic echocardiographic parameters. Results. According to all of the used cognitive scales, the same factors were independent predictors of cognitive deterioration during the first year after ischemic non-lacunar strokes in patients with AF – severe leukoaraiosis (Fazekas scale score >3), reduced left ventricle ejection fraction and increased left atrium size. The optimal thresholds of left ventricle ejection fraction values for predicting cognitive deterioration, depending on the cognitive scale, were within the interval of 41–48%, whereas the optimal threshold of left atrium size for predicting cognitive deterioration, regardless of the scale used, was the same – 41 mm. Conclusions. Independent predictors of cognitive deterioration in AF patients during the first year after ischemic non-lacunar strokes are leukoaraiosis, low left ventricle ejection fraction, and high left atrium size.